PERAN KELEKATAN ORANG TUA DAN SELF-ESTEEM TERHADAP DEPRESI REMAJA DENGAN KECENDERUNGAN BUNUH DIRI - Maulidiah, Risma Nasiatul; Astriani, Defi; Pradana, Hengki Hendra; Purwaningrum, Devia (Jurnal Psimawa : Diskursus Ilmu Psikologi dan Pendidikan, 2025)
This study aims to assess the role of parental attachment and self-esteem on adolescent depression with suicidal tendencies. A quantitative approach was used with simple linear regression and multiple linear regression analysis. Subjects totaled 100 adolescents aged 15 and 21 years who had thoughts of ending life. The results of the first hypothesis analysis showed a significant effect of parental attachment on depression by 41.9% with the acquisition of the calculated t value of -8.141 and a significance value of 0.00. The results of the second hypothesis test regarding the effect of self-esteem on depression get a t value of -9.116 and a significance value of 0.00, which means that self-esteem has a significant influence on depression with a large influence of 56.4%. While testing the third hypothesis which gets the calculated f value of 62.740 and the R-squared value of 0.564 implies that 56.4% of adolescent depression with suicidal tendencies is influenced by parental attachment and self-esteem, while the remaining 43.6% is influenced by other variables.